Evaluation of Antibiotic Prophylaxis Regimens in Gynecological Surgeries in a Referral Teaching Hospital: A Cross Sectional Study - Farnaz Naeimzadeh; Parvin Bastani; Elnaz Shaseb (Research Center for Rational Use of Drugs (RCRUD), 2021)
Background: Drug utilization Evaluation is the main tool to assess the clinical and economic effects of drug on health-care system. The aim of the current study is to evaluate the regimens of antibiotic prophylaxis in common gynecological surgeries in a referral teaching hospital Methods: This cross-sectional study was done in Alzahra hospital, Tabriz, Iran, from July 2017 to December 2017. Patients who received antibiotics as surgical site infection prophylaxis were enrolled. Data were collected from patients' medical records and adherence rate to the American Society of Health-System Pharmacists (ASHP) guideline was studied as the primary endpoint. Results: A total of 210 patients who undergoes common gynecological surgeries were evaluated. Cesarean section (58.6%) and total abdominal hysterectomy (28.1%) were the majority of surgeries. The type of administered antibiotic was adherent to guideline in 71.4%. Doses and duration of prescribed antibiotic (Cefazolin, the most prescribed antibiotic) were not in accordance with the guideline in 100%. Only in 58%, the time of antibiotic administration was corrected. Conclusion: In this study, the misuse of antibiotics in most cases was documented in terms of type, dose and duration of drug administration in Al-Zahra Hospital. It seems necessary to publish evidence-based guidelines and monitor their proper implementation, not only to reduce costs but also to combat antibiotic resistance.